Seamless Handover between Bluetooth and WIFI Using Packet Content Transfer Method (International Journal of Engineering and Computer Science, 2013)
Next generation wireless communications will likely rely on integrated networks consisting of multiple wireless technologies. Hybrid networks based, for instance, on systems such as Bluetooth and WiFi technologies can combine their respective advantages on coverage and data rates. In such environment, WiFi/Bluetooth should seamlessly switch from one network to another, in order to obtain improved performance or at least to maintain a continuous wireless connection. This paper proposes a new user algorithm for handover between Bluetooth and Wifi, which combines a trigger to continuously maintain the connection and another one to maximize the user throughput . Moreover, we detail the implementation of that algorithm follow packet content transfer method and session transfer among heterogeneous deployment.